2000
DOI: 10.1097/00004647-200004000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Model of Blood–Brain Transfer of Oxygen Explains Nonlinear Flow-Metabolism Coupling During Stimulation of Visual Cortex

Abstract: The coupling between cerebral metabolic rate of oxygen (CMRO2) and blood flow (CBF) in response to visual stimulation was evaluated by means of a model of oxygen delivery. The model predicted a nonlinear relationship between stimulus-evoked changes of oxygen consumption and blood flow. The magnitude of the CMRO2/CBF ratio index (IO2) was used to indicate the degree of flow-metabolism coupling prevailing in specific areas of the brain during physiological stimulation. Therefore, the index provided a measure of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
126
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(148 citation statements)
references
References 31 publications
21
126
1
Order By: Relevance
“…However, at 8 Hz stimulation frequency, CMRO 2 increase was only 5% whereas the CBF increase reached 42%. 78 This PET observation has been confirmed with MRI by Lin et al 98 Other studies have found tight coupling of CBF and CMRO 2 with varied stimulus paradigms. For example, in a recent study, Leontiev et al 99 did not find a significant difference in CBF/CMRO 2 coupling between two visual stimuli that activate different neuron populations characterized histologically by differences in cytochrome c distribution.…”
Section: Uncoupling Of Cerebral Blood Flow and Cerebral Metabolic Ratmentioning
confidence: 57%
See 1 more Smart Citation
“…However, at 8 Hz stimulation frequency, CMRO 2 increase was only 5% whereas the CBF increase reached 42%. 78 This PET observation has been confirmed with MRI by Lin et al 98 Other studies have found tight coupling of CBF and CMRO 2 with varied stimulus paradigms. For example, in a recent study, Leontiev et al 99 did not find a significant difference in CBF/CMRO 2 coupling between two visual stimuli that activate different neuron populations characterized histologically by differences in cytochrome c distribution.…”
Section: Uncoupling Of Cerebral Blood Flow and Cerebral Metabolic Ratmentioning
confidence: 57%
“…of arterial blood 9,000 nmoL/mL Glucose conc. of arterial blood 5,000-6,000 nmoL/mL 53 Oxygen extraction fraction 30%-55% 3,5,6,27,75,93 Glucose extraction fraction 8%-15% ATP concentration of brain tissue 1,000-3,000 nmoL/mL 124,137,138 Total ADP concentration of brain tissue 300 nmoL/mL 124,138 Free ADP concentration of brain tissue 30-35 nmoL/mL [121][122][123] PCr concentration of brain tissue 4,000-5,000 nmoL/mL 123,124,138 Diffusion constant for O2 in brain 78 Assuming mitochondrial oxygen tension close to zero (meaning so low that any further reduction would limit oxidative metabolism), the driving force for oxygen delivery, the gradient between the capillary and mitochondria, can only be increased by an increase in capillary oxygen tension, which in turn requires a decrease of the oxygen extraction fraction. Later, the observation of constant CMRO 2 during pharmacological reductions of CBF led to a modification of the model by incorporating potential changes of cytochrome c oxidase affinity to oxygen during increases in neuronal activity.…”
Section: Differences Of Oxygen and Glucose Supplymentioning
confidence: 99%
“…Previous studies have shown that conventional compartment models cannot be fitted to experimental data unless oxygen transport characteristics (dubbed 'PS area product', 'effective diffusivity', 'diffusion capacity', or 'conductance') are allowed to vary during physiologic stimuli. 8,9,12,14 It has been suggested that increased capillary oxygen tension, hematocrit, changes in blood volume, or capillary recruitment 8,9,14 may explain these observations, but the existence of such mechanisms remains controversial. 11 Debates over whether the oxygen conductance/PS product, in this case for oxygen, can change during functional activation typically emerge from structural interpretations of this quantity.…”
Section: Discussionmentioning
confidence: 99%
“…They speculated that such variations in oxygen conductance are linked to differences in CBF response, and possibly subject to local regulation. 9 The models above assumed negligible oxygen tension (pO 2 ) in tissue, whereas measurements suggest that interstitial pO 2 in brain tissue is in fact roughly 25 mm Hg, albeit with high microregional heterogeneity. 5 Tissue pO 2 affects the oxygen concentration gradient between blood and tissue, and therefore net oxygen extraction.…”
Section: Introductionmentioning
confidence: 99%
“…Several works have modelled the relationship between ( ) m t and ( ) f t (Buxton and Frank, 1997;Hyder et al, 1998;Vafaee and Gjedde, 2000;Zheng et al, 2002;Takuya et al, 2003). Particularly, the oxygen limitation model proposed by Buxton and Frank (1997) has been widely employed as part of biophysical models of the generation of the BOLD signal (Buxton et al, 1998;Friston et al, 2000;Friston et al, 2003;Babajani and Zoltanian-Zadeh, 2006;Riera et al, 2006;Riera et al, 2007;Babajani et al, 2008;Blockley et al, 2009):…”
Section: Modelling Temperature Changesmentioning
confidence: 99%